2008
DOI: 10.1017/s109285290001676x
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole as Augmentation Treatment of Refractory Generalized Anxiety Disorder and Panic Disorder

Abstract: Introduction:Individuals with anxiety disorders often remain symptomatic despite treatment with a first-line pharmacologic agent. More research examining pharmacotherapy augmentation strategies to improve outcomes is needed.Methods:In an 8-week, open-label, prospective augmentation study, we examined the efficacy and tolerability of the novel antipsychotic agent aripiprazole for adult outpatients with generalized anxiety disorder (n=13) or panic disorder (n=10) who remained symptomatic despite treatment for at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 0 publications
0
37
0
1
Order By: Relevance
“…Previous studies with other atypical antipsychotics like ariprazole, olanzapine, risperidone and quetiapine have shown similar results in improving HAM-A. [30][31][32][33] The unique therapeutic profi le of amisulpride has proven diffi cult to explain in light of its known pharmacological profi le. There is some evidence that amisulpride has some selectivity for presynaptic dopamine autoreceptors and exhibits limbic versus striatal selectivity, particularly at low doses, and it has been suggested that this might account for its therapeutic profi le.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies with other atypical antipsychotics like ariprazole, olanzapine, risperidone and quetiapine have shown similar results in improving HAM-A. [30][31][32][33] The unique therapeutic profi le of amisulpride has proven diffi cult to explain in light of its known pharmacological profi le. There is some evidence that amisulpride has some selectivity for presynaptic dopamine autoreceptors and exhibits limbic versus striatal selectivity, particularly at low doses, and it has been suggested that this might account for its therapeutic profi le.…”
Section: Discussionmentioning
confidence: 96%
“…Although the results are encouraging, it should be noted this trial was not in patients with treatment-refractory GAD. Two small open-label trials of aripiprazole augmentation for treatment-resistant GAD reported a significant reduction in symptoms (51,89), but these preliminary data require confirmation in larger controlled investigations. Ziprasidone monotherapy or augmentation was studied in an RCT of 62 patients with refractory GAD and was not found to be superior to placebo (90).…”
Section: Antipsychoticsmentioning
confidence: 96%
“…A more recent randomized, rater-blinded trial (Nϭ56) found risperidone monotherapy equivalent to paroxetine (50). An open-label study of patients with refractory panic disorder or generalized anxiety disorder (GAD) found that aripiprazole augmentation of an SSRI and/or benzodiazepine significantly reduced anxiety (51). The only data on ziprasidone for refractory panic disorder is a small case series with positive results (52).…”
Section: Antipsychoticsmentioning
confidence: 99%
“…With growing evidence for the involvement of dopamine as a neuromodulator in the development of fear conditioning, a few studies have examined the role of aripiprazole as a potential adjunct in standard SSRI therapy for GAD (Pezze and Feldon, 2004). Worthington et al (2005) and Hoge et al (2008) found significant global improvements in patients with resistant GAD treated with adjunctive aripiprazole therapy, and Menza et al (2007) found a reduction in anxiety symptoms as well as the secondary outcome of improvement in depressive symptoms. Atypical antipsychotics have been used off-label to augment SSRI therapy for obsessive-compulsive disorder (OCD), and two recent small studies have indicated that aripiprazole is effective for this indication (Matsunaga et al, 2011;Higuma et al, 2012).…”
Section: Introductionmentioning
confidence: 99%